The choice of bachelor’s program in telecommunications and computer technology - Stefanova, Tereza (Yearbook Telecommunications, 2021)
The aim of the article is to show the influence of the graduated secondary education for the choice of the bachelor's program "Telecommunications and Computer Technology" from the Telecommunication’s Department, NBU. The article presents some of the results of a survey conducted among students of the bachelor's program. The presented data are for students who started their education during the academic years from 2016 to 2019. As a result of the study, it was found that the students enrolled in the bachelor's program most often have graduated from vocational technical high schools in this field. Together with graduates of other vocational high schools, they are approximately half of the students who choose this bachelor's program.The study will contribute to anticipating the preliminary preparation of students who have chosen a bachelor's program in "Telecommunications and Computer Technology" and to improve their future education.